Environmental justice and U.S. Forest Service hazardous fuels reduction: A spatial method for impact assessment of federal resource management actions. (January 2018) - Adams, Mark D.O.; Charnley, Susan
Abstract: Natural resource managers of federal lands in the USA are often tasked with various forms of social and economic impact analysis. Federal agencies in the USA also have a mandate to analyze the potential environmental justice consequences of their activities. Relatively little is known about the environmental justice impacts of natural resource management in rural areas. Quantitative environmental justice analyses have so far heavily favored urban populations, in part owing to the difficulty of quantitative analysis of rural U.S. Census data. We developed a spatial method for integrating rural U.S. Census data with natural resource management data to address this gap. The method learns from methodological advances in overcoming the spatial limitations of Census data, but prioritizes a simple, efficient technique that is applicable not only for identifying potential environmental justice problems, but also to a potentially broad spectrum of natural resource management activities and spatial scales. We pilot test the method by analyzing the hazardous fuels reduction activities of two national forests in central Oregon, USA. We find no evidence of systematic environmental justice issues on either forest, but identify local areas that warrant additional investigation. Highlights: U.S. federal agencies must assess the environmental justice (EJ) implications of their actions. EJ impacts of natural resource management area poorly documented. A method for conducting preliminary quantitative EJ assessments of natural resource management is proposed. Problems encountered in quantitative analysis of fine-scale rural population data are addressed. The method is applicable to social impact assessment of many resource management activities.